(untitled) (Journal of Architectural Design, 2022)
The article deals with the control of non-cohesive soils. The currently existing definitions of the control parameters for laying soils at each facility are individual and require extensive experimental work to justify the control parameters for laying soils in the body of the dam. This takes into account a huge number of parameters: grain composition, humidity, layer thickness, density, etc.